Quantitative PCR to Discriminate Between Pneumocystis Pneumonia and Colonization in HIV and Non-HIV Immunocompromised Patients - Sarasombath, Patsharaporn T.; Thongpiya, Jerapas; Chulanetra, Monrat; Wijit, Sirirat; Chinabut, Pisith; Ongrotchanakun, Jeerawan; Jitmuang, Anupop; Wanachiwanawin, Darawan (Frontiers in Microbiology, 2021)
Pneumocystis pneumonia (PCP) is an opportunistic infection that commonly occurs in immunocompromised individuals. A definite diagnosis of PCP can be made only when the organism is identified in a respiratory specimen. It remains unclear whether qPCR can differentiate patients with PCP from those with Pneumocystis jirovecii colonization. In this study, we retrospectively collected data from HIV and non-HIV patients during 2013-2019.. A diagnosis of definite, probable PCP, or PCP excluded was made based on clinical criteria, radiological reports, and 3 standard laboratory staining methods with blinding to qPCR data. Data from qPCR that was performed to determine the fungal burden (DNA copies/µl) in the BAL specimens of 69 HIV and 286 non-HIV patients were then obtained and reviewed. Receiver Operating Characteristic (ROC) curve analysis was performed to determine the upper and lower cut-off values for PCP diagnosis in HIV and non-HIV groups. In the non-HIV group, the lower cut-off value of 1,480 DNA copies/µl yielded a sensitivity of 100% (95% confidence interval [CI], 91.0-100), specificity of 72.9% (95% CI, 64.0-80.7), a positive predictive value (PPV) of 54.9% (95% CI, 47.6-62.1) , and a negative predictive value (NPV) of 100% with Youden index of 0.73 for PCP diagnosis. In this group, the upper cut-off value of 9,655 DNA copies/µl, showed the sensitivity of 100% (95% CI, 91.0-100) and specificity of 95.8% (95% CI, 90.4-98.6) with PPV of 88.6% (95% CI, 76.8-94.8), and a NPV of 100% with Youden index of 0.96 for PCP diagnosis. Regarding the HIV group, the lower cut-off value of 1,480 DNA copies/µl showed the sensitivity of 100% (95% CI, 92.5-100%) and specificity of 91.7% (95% CI, 61.5-99.8) with PPV of 97.9% (95% CI, 87.8-99.7), and a NPV of 100% with Youden index of 0.92 for PCP diagnosis. The sensitivity and specificity of the upper cut-off value of 12,718 DNA copies/µl in this group were 97.9% (95%CI, 88.7-100) and 100% (95%CI, 73.5-100), respectively. The values above the upper cut-off point had a PPV of 100% (95% CI, N/A), and a NPV of 92.3% (95% CI, 63.3-98.8) with Youden index of 0.98 for PCP diagnosis in the HIV group.